1968
DOI: 10.1254/jjp.18.518
|View full text |Cite
|
Sign up to set email alerts
|

Microperfusion of Henle’s Loop in the Kidney of the Adrenalectomized Rat

Abstract: It is now generally accepted that urine is osmotically concentrated by the mammalian kidney through the operation of a countercurrent mechanism in the renal medulla and that active sodium transport out of the ascending limb of Henle's loop plays an important role for this mechanism. On the other hand, it has been reported that in the adrenalectomized rat urine volume is decreased and the corticomedullary osmotic gradient lowered (1-3). The present experiments, therefore, were an attempt to investigate the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…When tubule flow rate was held constant by microperfusion, Murayama et al (7) found that large acute doses of cortisol did not have a significant effect on solute reabsorption in the loop ofHenle. In contrast, in a more recent microperfusion study, dexamethasone increased sodium reabsorption in the loop of Henle; however, the physiological significance ofthis effect is questionable steroid was given chronically to adrenalectomized rats (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When tubule flow rate was held constant by microperfusion, Murayama et al (7) found that large acute doses of cortisol did not have a significant effect on solute reabsorption in the loop ofHenle. In contrast, in a more recent microperfusion study, dexamethasone increased sodium reabsorption in the loop of Henle; however, the physiological significance ofthis effect is questionable steroid was given chronically to adrenalectomized rats (5).…”
Section: Discussionmentioning
confidence: 99%
“…Addisonian patients and animals deficient in these hormones have a decreased ability to generate a maximally concentrated urine (1)(2)(3). Sodium reabsorption by the loop of Henle is decreased in adrenalectomized rats, which suggests that part of the defect in the ability to concentrate the urine results from a reduction in the single effect of the countercurrent multiplier in the thick ascending limb of Henle's loop (4)(5)(6)(7)(8). In addition, some but not all studies have shown that adrenalectomy reduces potassium reabsorption in the loop of Henle (6,9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of this experiment was almost same as that previously reported (1). A proximal tubule of anesthetized rat (Nembutal 30 mg/kg i.v.)…”
mentioning
confidence: 99%
“…The loop of Henle was perfused according to the method of Cortney et al (8) as has previously described (9). The perfusion pipet was placed in a late segment of a proximal tubule and a collection was made from the early segment of the distal tubule of the same nephron.…”
mentioning
confidence: 99%